PENGARUH TERAPI RELAKSASI BENSON PADA PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS DELI TUA TAHUN 2025 - Hasian, Muhammad Tsawaby; Rosaulina, Meta (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Relaxation therapy is among the non-pharmacological methods that has been proven effective in addressing various health problems, including type 2 diabetes mellitus. One approach that can be applied is Benson relaxation therapy, which combines deep breathing techniques and positive suggestions to help reduce stress. This research aims to examine the effect of Benson relaxation therapy on lowering blood sugar levels in patients with type 2 diabetes mellitus. The methodology employed in this study was a quasi-experimental design with a one-group pre-post test approach. The total sample size for this study comprised 37 respondents, selected through purposive sampling techniques. The instrument utilized was an observation sheet, and testing was carried out with the Wilcoxon test. The findings indicated a significant decrease in blood sugar levels after the application of Benson relaxation therapy for 2 weeks (p<0.05) in type II diabetes mellitus patients at the Deli Tua Health Center. This decrease is due to the effect of therapy in reducing stress, that contributes significantly to the regulation of stress hormones and glucose metabolism. In conclusion, Benson relaxation therapy is effective as an additional therapy to help lower blood glucose levels in individuals with type 2 diabetes mellitus.